The changes of NLRs family members in the brain of AD mouse model and AD patients - Li, Zehan; He, Yanling; Zhang, Jingdan; Yang, Jing; Cheng, Jinbo; Zhang, Xuewu (Frontiers in Immunology, 2025)
IntroductionAlzheimer’s disease (AD), a prevalent neurodegenerative disease, is primarily characterized by progressive neuron loss and memory impairment. NOD-like receptors (NLRs) are crucial for immune regulation and maintaining cellular homeostasis. Recently, NLRs have been identified as important contributors to neuroinflammation, thus presenting a potential approach for reducing inflammation and slowing AD progression.MethodsWe use quantitative RT-PCR to detect levels of NLR family members in AD mouse model. Additionally, we use immunofluorescence to detect NLRP3 expressions in microglia surrounding Aβ plaques in AD mouse model and human AD patients.ResultsIn this study, we examined the expression of NLR family members in the human AD database, and found increased levels of CIITA, NOD1, NLRC5, NLRP1, NLRP3, NLRP7, NLRP10, NLRP12, and NLRP13 in hippocampus tissue in patients with AD, along with increased levels of NOD1, NLRC5, NLRX1, NLRP3, and NLRP7 levels in frontal cortex tissue. Furthermore, through detecting their levels in AD mouse model, we found that NLRP3 levels were significantly increased. Additionally, we found that NLRP3 expressions were mainly elevated in microglia surrounding Aβ plaques in AD mouse model and human AD patients.DiscussionThese findings highlight the potential important role of NLRP3 in AD pathology, offering new therapeutic targets and interventions.